Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Menerapkan Metode AHP dan MOORA - Mochamad Dedy Subekti Rahardjo (STMIK Budi Darma, 2024)
This decision support system research method is used for racing in order to help vocational high schools (SMK) in determining the selection of outstanding teachers. In this selection of outstanding teachers, the method of selection is still using a manual system, which is based on observations from the principal directly by selecting teachers who are considered to have excellence based on predetermined criteria, for example having special achievements, having perseverance, activeness in school, attendance, and social relationships. For this research, the methods used in selecting outstanding teachers are Analytical Hierarchy Process (AHP) for weighting and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) in ranking purposes. The result for this research is that the combination of AHP and MOORA methods in determining outstanding teachers can be used. SPK can show information according to what the user enters correctly.